Lonely sensational icons: semantic neighbourhood density, sensory experience and iconicity. Issue 1 (2nd January 2018) - Sidhu, David M.; Pexman, Penny M.
ABSTRACT: Perry, Perlman, and Lupyan (2015. Iconicity in English and Spanish and its relation to lexical category and age of acquisition. PLoS One, 10, e0137147. doi:10.1371/journal.pone.0137147 ) found that a sample of English words was rated as being slightly iconic, on average, with words varying in their iconicity. Thus, the relationship between word form and meaning does not seem to be categorically arbitrary. We investigated factors that might explain variation in iconicity: specifically, that concepts with sparser semantic neighbourhoods have more iconic word forms, and that concepts with more sensory information are more likely to have iconic word forms (as in Winter, Perlman, Perry, & Lupyan, in press. Which words are the most iconic? Iconicity in English sensory words. Interaction Studies . Retrieved from http://sapir.psych.wisc.edu/papers/winter_perlman_perry_lupyan_interaction-studies.pdf), even after accounting for age of acquisition (AoA; Kuperman, Stadthagen-Gonzalez, & Brysbaert, 2012. Age-of-acquisition ratings for 30, 000 English words. Behavior Research Methods, 44, 978–990. doi:10.3758/s13428-012-0210-4 ). We found support for both predictions: words with sparser semantic neighbourhoods (ARC; Shaoul & Westbury, 2010. Exploring lexical co-occurrence space using HiDEx. Behavior Research Methods, 42, 393–413. doi:10.3758/Brm.42.2.393 ), and greater associated sensory experience (SER; Juhasz & Yap, 2013. Sensory experience ratings for over 5, 000 mono-and disyllabic words. Behavior Research Methods, 45, 160–168. doi:10.3758/s13428-012-0242-9 ), were more iconic, even after accounting for AoA. ARC was also found to moderate SER. These results further our appreciation of iconicity as a general property of the lexicon.